1991
DOI: 10.1093/genetics/129.4.1073
|View full text |Cite
|
Sign up to set email alerts
|

Structure and transcription of the singed locus of Drosophila melanogaster.

Abstract: Developmental and genetic studies of the singed gene of Drosophila melanogaster indicate that the gene has a role in somatic cells during the formation of adult bristles and hairs, and in the female germline during oogenesis. During metamorphosis a single 3.6-kilobase (kb) RNA is made, and this RNA is also present in adults and early embryos. Early embryos and adult females have additional 3.3- and 3.0-kb RNAs. The RNAs differ only in the length of the 3' untranslated region and a single gene product of 57 kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Western and immunofluorescence analyses showed that the singed protein is absent from the nurse cells (Cant et al, 1994). Since the molecular defect of this mutation is unknown (Paterson and O'Hare, 1991), tiny amounts of the protein, beneath the limit of detection by these techniques, could be present in these cells. The phenotype described by Cant et al (1994) was a severe reduction in cytoplasmic actin bundles, but the ring canals and subcortical actin appeared to be like the wild type.…”
Section: Light Microscopy Of Actin Bundles In Nurse Cellsmentioning
confidence: 99%
“…Western and immunofluorescence analyses showed that the singed protein is absent from the nurse cells (Cant et al, 1994). Since the molecular defect of this mutation is unknown (Paterson and O'Hare, 1991), tiny amounts of the protein, beneath the limit of detection by these techniques, could be present in these cells. The phenotype described by Cant et al (1994) was a severe reduction in cytoplasmic actin bundles, but the ring canals and subcortical actin appeared to be like the wild type.…”
Section: Light Microscopy Of Actin Bundles In Nurse Cellsmentioning
confidence: 99%
“…Some of the sites of mutation for these alleles have been described (Paterson and O'Hare, 1991;Roiha et al, 1988). Transcription of singed in singed 3 uses a cryptic prometer and starts 200-bp closer to the o/fE promoter; the developmental profile of the cryptic promoter allows adequate expression during oogenesis but not bristle formation (Paterson and O'Hare, 1991). cn;ry 5°6 flies were used as the wild type control.…”
Section: Drosophila Stocksmentioning
confidence: 99%
“…In sterile singed mutants, singed ~ and singed36% the 57-kD protein was absent or nearly absent. Three transcripts are generated from the singed locus that differ only in the 3'-untranslated region and encode the same 57-kD protein (Paterson and O'Hare, 1991). The absence of protein in severe, sterile singed alleles suggested that all transcripts are affected.…”
Section: Monoclonal Antibodies Recognize a 5 7-kd Protein That Is Reduced In Singed Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent cloning of fascin cDNAs from Strongylocentrotus purpuratus demonstrated that fascins are widely distributed throughout the animal kingdom (Bryan et al, 1993). Sequence comparison showed that echinoid fascin is homologous to the product of the Drosophila singed gene (Paterson and O'Hare, 1991), which is important in both mechanosensory bristle development and oogenesis. Overton showed that developing bristles contain a central core of mi-* The costs of publication of this article were defrayed in part by the payment of page charges.…”
mentioning
confidence: 99%